2019
DOI: 10.7759/cureus.5105
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Open Appendectomy and Laparoscopic Appendectomy in Perforated Appendicitis

Abstract: Introduction Laparoscopic appendectomy for nonperforated appendicitis is associated with improved outcomes. This study compares laparoscopic appendectomy and open appendectomy in cases of a perforated appendix by assessing surgical site infection, mean operating time, and length of hospital stay. Materials and methods This study was a prospective randomized study conducted at the Department of Surgery, Holy Family Hospital, Rawalpindi, Pakistan, from January 2016 to January 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 25 publications
3
23
1
1
Order By: Relevance
“…The results contradict the findings from other research studies. The findings from the other research studies indicated that open appendectomy is associated with a shorter hospital stay than laparoscopic appendectomy [13][14][15]. Furthermore, the operative time for the two surgical procedures was considerably shorter than the operative time reported by other research studies.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The results contradict the findings from other research studies. The findings from the other research studies indicated that open appendectomy is associated with a shorter hospital stay than laparoscopic appendectomy [13][14][15]. Furthermore, the operative time for the two surgical procedures was considerably shorter than the operative time reported by other research studies.…”
Section: Discussionmentioning
confidence: 69%
“…Research studies that compared the operative time between the surgical procedures reported the same findings that the duration of open appendectomies was shorter than that of laparoscopic appendectomy [13][14][15]. Shimoda et al (2018) noted that the longer operative time in laparoscopic appendectomy was due to the associated complications and largely dependent on the surgeon's skill and experience [16].…”
Section: Discussionmentioning
confidence: 99%
“…Seqsaqa et al, 2020. reported that the need for intraperitoneal drain insertion was significantly lower with LA than OA (p = 0.001). This significance was also reported by Horvath et al 2017; they explained that the laparoscopic technique offers a good vision to the entire abdomen and that enables the surgeon to achieve a careful suction from every quadrant having collections [30] Also, Nazir et al, 2019 [31] Additional studies suggest the laparoscopic approach is associated with longer operating times than an open appendectomy. These results were in contradiction to ours.…”
Section: The Main Results Of This Study Were As Followingmentioning
confidence: 64%
“…This was statistically significant too. Nazir A et al [13] also reports increase wound infection rates for open appendicectomy (27.69%) when compared to laparoscopic appendicectomy (10.77%). In our study SSI incidence is higher than reported by Nazir A et al [13] but the SSI in laparoscopic group is much less.…”
Section: Discussionmentioning
confidence: 92%